MANAJEMEN PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA TANGRAM PADA SISWA SD DI KEPAHIANG - Ismail Ismail Ismail (UNIVERSITAS BENGKULU, 2016)
The purpose of this research was to know mathematics learning management using tangram media to student. The subjects this research were six grade of SD Negeri 04 Kepahiang in the. This research used the classroom action research. The techniques of collecting the data used questionnaire, observation, and the result of test. The result of this research found that: an increasein the creativity of mathematical ability the students to use tangram media, the students attitudes is positive towards of mathematics, the students creative of abilities has increased.Keyword: media, tangram, management